Application of Water Conservation Concept in X Apartment Bogor Regency - Eka Wardhani; Windya Sefniza Putri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
The increase of population in Bogor Regency is directly proportional to the rapid development of residential building construction, one of which is apartment buildings. This resulted in the need for clean water also increased. Water conservation is an effort to maintain the availability of clean water in sufficient quality and quantity to serve the current and future needs of clean water. The application of the concept of water conservation in Apartment X in Bogor Regency can be done using WAC 2 (Water Fixtures) and WAC 3 (Water Recycle). Apartment X building has a building population of 998 people with daily clean water needs of 91,545 liter/day. The wastewater generated by the apartment building is 73,236 liter/day. It is estimated that the implementation of water conservation could save the use of clean water by 28.08% or around 25,701.42 liter/day.